Clear cell hidradenoma of the hand: A case report in an 83-year old patient. (2020) - Efremov, Kristian; Caterini, Alessandro; Petrungaro, Lidio; De Maio, Fernando; Di Prete, Monia; Ferlosio, Amedeo; Tresoldi, Ilaria; Farsetti, Pasquale
Highlights: Clear Cell Hidradenoma (CCH) is a benign tumor of the sweat glands that very rarely appear on the hand. CCH needs to be considered as a possible diagnosis for small subcutaneous masses on the extremities in all ages. Accurate surgical excision is the treatment of choice, to avoid recurrence. Histological analysis is fundamental for a correct diagnosis. Abstract: Introduction: Clear cell hidradenoma (CCH) is a superficial adnexal tumor of the sweat glands. It generally appears on the trunk or scalp and is uncommon on the upper and lower limbs; it is extremely rare on the hand. CCH tend to be benign, with low malignancy risk. Treatment is based on complete surgical excision. We report a rare case of a CCH of the palm of the hand in an 83-year old patient. Presentation of case: An 83-year old male patient presented with a small mass on the palmar surface of his left hand, which was progressively increasing over 5 years. The tumor was surgically excised after sonography and sent for histologic examination, based on which diagnosis of CCH was made. Three months after surgery, the patient had no recurrence and was symptom free. Discussion: CCH is a rare tumor of the distal extremities and to the best of our knowledge, only one case of this tumor on the hand has been reported. Our case represents a rare CCH located at the palm of the hand, which was successfully surgical excised without recurrence. Therefore, CCH needs to be considered in the differential diagnosis when encountering masses on the distal extremities. Hidradenocarcinoma is the malignant variant that arises from the same cells. Conclusion: We report the second case of CCH on the palmar surface of the hand. Treatment of choice is surgical excision, followed by histological analysis and close follow-up for recurrence.